Socialization of the "Ice-Breaking" Game in Building Students’ Concentration in Learning English at SMA Negeri 1 Sukoharjo - Tira Nur Fitria (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This community service activity aims to introduce icebreaking and socialize icebreaking to build student concentration in learning English. This community service program society is held on 12 January 2024 at SMA Negeri 1 Sukoharjo and involves 35 students of XII Bahasa.The demonstration method is crucial for direct, practical, and interactive learning. The lecturer from ITB AAS Indonesia introduces herself and invites the students to play ice-breaking games, including applause, number, and word games. The games include "Clap Game," "Total Number," and "Word Game." These activities not only improve students' geographic knowledge but also enhance their critical thinking and teamwork skills while having fun in a classroom setting. This activity involves a teacher explaining the rules of a word game, where students must guess the name of a city or country from clues given. Icebreaking is a popular method used in English language learning to create a fun, interactive, and supportive learning environment. Students respond positively to icebreakers, as they see it as an opportunity to interact with classmates, reduce awkwardness, and maintain a fun learning atmosphere. This approach helps students become more focused and engaged in learning English, overcoming anxiety and shyness. Teachers must be creative and brave to implement icebreaking activities outside the classroom, ensuring better interpersonal interactions and group dynamics between teachers and students. By incorporating icebreaking activities, teachers can enhance the overall learning process and foster brain optimization and creativity in their students.